Скандалы в высшем образовании (пер. с англ. И. Фридмана) - Делбанко, Эндрю (Вопросы образования / Educational Studies Moscow, 2010)
Книги, обсуждаемые в этой статье: 1. Equity and Excellence in American Higher Education by William G. Bowen, Martin A. Kurzweil, and Eugene M. Tobin, in collaboration with Susanne C. Pichler. University of Virginia Press, 453 pp. 2. The Price of Admission: How America’s Ruling Class Buys Its Way into Elite Colleges — and Who Gets Left Outside the Gates by Daniel Golden. Crown, 323 pp. 3. The Trouble with Diversity: How We Learned to Love Identity and Ignore Inequality by Walter Benn Michaels. Metropolitan, 241 pp. 4. Excellence Without a Soul: How a Great University Forgot Education by Harry R. Lewis. Public Affairs, 305 pp. 5. Our Underachieving Colleges: A Candid Look at How Much Students Learn and Why They Should Be Learning More by Derek Bok. Princeton University Press, 413 pp. 6. Powers of the Mind: The Reinvention of Liberal Learning in America by Donald N. Levine. University of Chicago Press, 299 pp.